2008
DOI: 10.1007/s10329-008-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Muscle architecture of the upper limb in the orangutan

Abstract: We dissected the left upper limb of a female orangutan and systematically recorded muscle mass, fascicle length, and physiological cross-sectional area (PCSA), in order to quantitatively clarify the unique muscle architecture of the upper limb of the orangutan. Comparisons of the musculature of the dissected orangutan with corresponding published chimpanzee data demonstrated that in the orangutan, the elbow flexors, notably M. brachioradialis, tend to exhibit greater PCSAs. Moreover, the digital II-V flexors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
(35 reference statements)
2
27
0
Order By: Relevance
“…Furthermore, living specimens would probably withstand the tensile strain and stresses experienced during locomotion mostly on their shoulder soft tissues such as muscles, ligaments, and tendons rather than directly on their scapulae. Even though shoulder muscle origin and insertions for hominoids are known (Diogo et al, ,,,; Diogo and Wood, ) and physiological cross‐sectional areas of some the muscles are available for some of the analyzed species (Veeger et al, ; Keating et al, ; Thorpe et al, ; Cheng and Scott, ; Carlson, ; Oishi et al, ; Michilsens et al, ; Peterson and Rayan, ; Myatt et al, ), the specific activation patterns are unknown for the majority of the species when performing the analyzed postures. These reasons ratified the decision of carrying out simpler comparative structural analyses instead of simulating in detail loading scenarios based on unknown or uncertain information.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, living specimens would probably withstand the tensile strain and stresses experienced during locomotion mostly on their shoulder soft tissues such as muscles, ligaments, and tendons rather than directly on their scapulae. Even though shoulder muscle origin and insertions for hominoids are known (Diogo et al, ,,,; Diogo and Wood, ) and physiological cross‐sectional areas of some the muscles are available for some of the analyzed species (Veeger et al, ; Keating et al, ; Thorpe et al, ; Cheng and Scott, ; Carlson, ; Oishi et al, ; Michilsens et al, ; Peterson and Rayan, ; Myatt et al, ), the specific activation patterns are unknown for the majority of the species when performing the analyzed postures. These reasons ratified the decision of carrying out simpler comparative structural analyses instead of simulating in detail loading scenarios based on unknown or uncertain information.…”
Section: Methodsmentioning
confidence: 99%
“…1999; Ogihara et al. 2005; Carlson, 2006) and orangutan (Payne, 2001; Oishi et al. 2008), although the muscle morphology of the hindlimb of these species has been more completely described (Thorpe et al.…”
Section: Introductionmentioning
confidence: 99%
“…While the inclusion of more muscles is not expected to significantly alter the weak relationships between total PCSA and functional performance, future characterization of these architectural parameters would provide a more complete picture of age-related PCSA loss and would allow for additional comparison of the vervet muscle structure to those obtained for other non-human primates. 2,6,11,17,29,30,33 Only female vervets were included in this study. Although it is unclear if hormonal imbalances due to aging or menstrual cycle phase affect the results of this study, previous work found that lean body mass in adult human women was approximately 64% of that in men from regardless of decade of life indicating that women and men lose muscle mass at approximately the same rate.…”
Section: Discussionmentioning
confidence: 99%